Translating Colloquial Idioms/Metaphors in The Catcher in the Rye: A Comparison of Metaphorical Meaning Retention in the Spanish and Catalan Texts - O'Mara, Michael (Miscelánea: A Journal of English and American Studies, 2007)
The use of colloquial idioms is one of the most unique and defining aspects of the idiolect of Holden Caulfield in The Catcher in the Rye. This research attempts to determine which of the two translations, Spanish and Catalan, retains more figurative/metaphorical meaning in their representations of such idioms. Our results would seem to suggest that the Catalan translation retains more figurative meaning. This translation employs on significantly more occasions lexicalized structures expressing similar metaphorical meaning, though differing in form while the Spanish translation, on significantly more occasions paraphrases or explains the idioms in question. This paper presents new findings as, to our knowledge, no studies have been carried out comparing the Spanish and Catalan texts in terms of figurative/metaphorical meaning retention in their representations of Holden Caulfield’s colloquial idioms.